Effect of nondipper hypertension on coronary artery disease progression in patients with chronic coronary syndrome - ELÇİK, Deniz (Turk J Med Sci, 2021)
BACKGROUND/AIM: It has been suggested that there is a significant progress in coronary artery disease (CAD) by many pathophysiological mechanisms. Nondipper hypertension (NDH) has been shown to have higher target organ damage and have a higher rate of cardiovascular mortality and morbidity. In this study, we investigated the effect of nondipper hypertension on the progression of coronary atherosclerosis. MATERIALS AND METHODS: A total of 186 patients who underwent coronary angiography twice between 6 months and 3 years were included in the study. Coronary angiography was repeated on the admission day due to angina or positive exercise test and the patients were divided into groups. RESULTS: Progression of coronary artery disease was detected in 58 of 186 patients. Seventy-one of the total patients were found to be nondipper hypertensive. Nondipper hypertension, hypertension, diabetes mellitus, low-density lipoprotein, and total cholesterol were found to be effective in the progression of CAD. Among these parameters, it was seen that nondipper hypertension and hyperlipidemia were the most important independent risk factors. CONCLUSION: Coronary artery disease is a progressive disease, and this progression depends on many reasons. In our study, we showed that nondipper hypertension is a new parameter that is effective in CAD progression.